2016
DOI: 10.1111/weng.12192
|View full text |Cite
|
Sign up to set email alerts
|

Pronoun deletion in Hong Kong English and Colloquial Singaporean English

Abstract: The question how substrate features and extralinguistic conditions interact in shaping contact varieties is an ongoing debate in the study of world Englishes. The present study tries to describe substrate influence by identifying an areally marked morphosyntactic feature, subject pronoun deletion, and comparing its occurrence and structural conditioning in two closely related varieties of English in Southeast Asia. Our results show that even in the typologically similar linguistic habitats of Hong Kong and Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For instance, despite the fact that, of all grammatical components, morphology and syntax have been traditionally considered the least vulnerable to the effects of language contact (Thomason and Kauffmann, 1988: 51-52), recent studies (e.g. Mukherjee and Gries, 2009;Schröter and Kortmann, 2016;Suárez-Gómez, 2017) have shown that contact languages or dialects tend to contain grammatical structures that are the result of transfer from one of the languages/dialects involved in the contact situation to the other(s). These innovations introduce new variants in the grammar and, therefore, increase its complexity from a systemic point of view by expanding the set of rules/constructions available.…”
Section: Syntactic Complexitymentioning
confidence: 99%
“…For instance, despite the fact that, of all grammatical components, morphology and syntax have been traditionally considered the least vulnerable to the effects of language contact (Thomason and Kauffmann, 1988: 51-52), recent studies (e.g. Mukherjee and Gries, 2009;Schröter and Kortmann, 2016;Suárez-Gómez, 2017) have shown that contact languages or dialects tend to contain grammatical structures that are the result of transfer from one of the languages/dialects involved in the contact situation to the other(s). These innovations introduce new variants in the grammar and, therefore, increase its complexity from a systemic point of view by expanding the set of rules/constructions available.…”
Section: Syntactic Complexitymentioning
confidence: 99%
“…For instance, despite the fact that, of all grammatical components, morphology and syntax have been traditionally considered the least vulnerable to the effects of language contact (Thomason and Kauffmann, 1988: 51-52), recent studies (e.g. Mukherjee and Gries, 2009;Schröter and Kortmann, 2016;Suárez-Gómez, 2017) have shown that contact languages or dialects tend to contain grammatical structures that are the result of transfer from one of the languages/dialects involved in the contact situation to the other(s). These innovations introduce new variants in the grammar and, therefore, increase its complexity from a systemic point of view by expanding the set of rules/constructions available.…”
Section: Syntactic Complexitymentioning
confidence: 99%